IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI DALAM MEMENUHI KEBUTUHAN BELAJAR PESERTA DIDIK DI ERA KURIKULUM MERDEKA PADA SEKOLAH DASAR DI KOTA SEMARANG - Salsa Bella; S.Sumarno; Dwi Sartika (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research evaluates the implementation of differentiated learning in the Merdeka Curriculum in class V at an elementary school in Semarang City. Lifelong education emphasizes the importance of creating a safe and comfortable learning environment, as well as developing academic and non-academic competencies. The Merdeka Curriculum, implemented in 2021, focuses on student-centered learning, with initial, formative, and summative assessments for comprehensive evaluation. Differentiated learning adapts teaching methods to students' individual abilities, interests, and learning needs, making it relevant in this context. Descriptive qualitative research methods were used to collect data through observation, interviews, and documentation analysis, involving 28 students and a homeroom teacher. The research results show that differentiated learning in the Merdeka Curriculum effectively increases student engagement, motivation, and academic achievement. Although there are challenges such as the need for more time and complex activity preparation, ongoing support through teacher training is essential to overcome these barriers. This research emphasizes the importance of accurate mapping of learning needs and synergy between teachers, parents, and communities for the success of differentiated learning. Proper implementation of differentiated learning in the Merdeka Curriculum not only improves academic achievement but also ensures that every student gets a meaningful and enjoyable learning experience. This study provides practical recommendations for improving the quality of learning according to the principles of the Independent Curriculum, which aims to create a learning environment that is dynamic and responsive to students' needs.